Pricing in asymmetric two-sided markets: A laboratory experiment - Jens Weghake; Mathias Erlei; Claudia Keser; Martin Schmidt (Technische Universität Clausthal, Abteilung für Volkswirtschaftslehre, 2018)
We conducted a laboratory experiment to study the price setting behavior in two-sided markets. We seek to answer two specific research questions: Do participants charge the equilibrium prices that can be derived from a theoretical model? How is the price setting affected by the characteristics of the Nash equilibrium? Our study shows that there are hardly any realizations of the Nash equilibrium. Participants seem to use simple heuristics. The increase in complexity caused by asymmetry has two effects: On the one hand, it makes finding the optimal pricing more difficult so that, on average, we find prices that are further away from optimal prices. On the other hand, higher complexity goes along with stronger signals against non-expedient heuristics so that, on an individual level, the equilibrium is reached in more markets.
Keywords: C72; C91; D43; L13; 330; two-sided market theory; experiment; duopoly; platform competition